The Current Trend of Culinary Learning from Basically and Self-taught with social media - winanti, Winanti; Fernando, Erick; Nurasiah, Nurasiah; Basuki, Sucipto; Hasna, Shofwatun; Riyanto, Riyanto (Journal of Applied Research In Computer Science and Information Systems, 2024)
The large amount of information that can be explored and obtained through social media makes social media one of the media currently most in demand by most internet users because of the ease of access and completeness of the information. The aim of this research is to explore how much social media is used to learn cooking and how effective social media is for learning culinary arts. This research involved 96 respondents and resulted in the most widely used social media being YouTube, namely 62 (65%) apart from Instagram, Facebook, Twitter, TikTok and Facebook. The research results stated that as many as 55 (57%) social media were used to search for information rather than for entertainment, learning, product promotion and status updates. Social media is considered more effective by 67 (70%) for finding information about culinary compared to other electronic media, especially through YouTube social media. No less important, social media is also able to increase user motivation to continue accessing social media compared to other media. In the future, questionnaires will be distributed to more respondents so that results can be maximized. It is possible that trends will change according to the needs of society at large